Three-dimensional analysis of the maxillary sinus according to sex, age, skin color, and nutritional status: A study with live Brazilian subjects using cone-beam computed tomography - Barros, Franciéllen de [UNESP]; Fernandes, Clemente Maia da Silva [UNESP]; Kuhnen, Barbara [UNESP]; Scarso Filho, José [UNESP]; Gonçalves, Marcelo [UNESP]; Gonçalves, Victor [UNESP]; Serra, Mônica da Costa [UNESP] (Elsevier, 2022)
Objective: To perform three-dimensional measurements (volume and area) of the maxillary sinus, from cone-beam computed tomography (CBCT) images, and to assess potential differences between the left and right sides and a correlation of the measurements to sex, age, skin color, and nutritional status. Design: CBCT images of 161 living Brazilian subjects of both sexes (89 women and 72 men) were used, and three-dimensional measurements of volume and area were made with the beta version of the DDS-Pro™ 2.14.2_2022 software (DPP Systems, Czestochowa, Poland). The inter- and intra-examiner reproducibility of measurements was evaluated with TEM, rTEM, and R. Results: Both maxillary sinus volume and area did not show significant differences between the left and right sides and between the sexes. Volume and area were significantly lower in the age group from 6 to 11 years than in the other two groups (p < 0.05). The measurements obtained for maxillary sinus volume and area were significantly higher in white individuals (p < 0.05), but they did not show significant differences (p > 0.05) regarding nutritional status (considering the body mass index - BMI). Conclusion: There were no statistically significant differences between the sexes, which does not allow recommending the use of maxillary sinus volume and area measurements to analyze sexual dimorphism, and the same occurs for BMI. However, such measures can help to estimate the age and skin color of individuals.
Keywords: 3D images; Cone-beam computed tomography; Forensic anthropology; Forensic dentistry; Human identification; Maxillary sinus